Exposure to Phthalates and Phenols during Pregnancy and Offspring Size at Birth - Philippat, Claire; Mortamais, Marion; Chevrier, Cécile; Petit, Claire; Calafat, Antonia M.; Ye, Xiaoyun; Silva, Manori J.; Brambilla, Christian; Pin, Isabelle; Charles, Marie-Aline; Cordier, Sylvaine; Slama, Rémy (Environmental health perspectives, 2012)
Background: Data concerning the effects of prenatal exposures to phthalates and phenols on fetal growth are limited in humans. Previous findings suggest possible effects of some phenols on male birth weight. Objective: Our aim was to assess the relationships between prenatal exposures to phthalates and phenols and fetal growth among male newborns. Methods: We conducted a case-control study on male malformations of the genitalia nested in two French mother-child cohorts with recruitment between 2002 and 2006. We measured, in maternal urinary samples collected between 6 and 30 gestational weeks, the concentrations (micrograms per liter) of 9 phenol (n = 191 pregnant women) and 11 phthalate metabolites (n = 287). Weight, length, and head circumference at birth were collected from maternity records. Statistical analyses were corrected for the oversampling of malformation cases. Results: Adjusted birth weight decreased by 77 g [95% confidence interval (CI): –129,–25] and by 49 g (95% CI:–86,–13) in association with a 1-unit increase in In-transformed 2,4-dichlorophenol (DCP) and 2,5-DCP urinary concentrations, respectively. Benzophenone-3 (BP3) In-transformed concentrations were positively associated with weight (26 g; 95% CI:–2 , 54) and head circumference at birth (0.1 cm; 95% CI: 0.0, 0.2). Head circumference increased by 0.3 cm (95% CI: 0.0, 0.7) in association with a 1-unit increase in In-transformed BPA concentration. For phthalate metabolites there was no evidence of monotonie associations with birth weight. Conclusions: Consistent with findings of a previous study, we observed evidence of an inverse association of 2,5-DCP and a positive association of BP3 with male birth weight.